TINGKAT ASPIRASI KARIR SISWA DI TINJAU DARI JENIS KELAMIN - Yusrial Chandra (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
Career apathy is very important to support the future / career of students, because it is a demand in life. Career aspiration is an individual orientation towards the desired career goals according to the desired conditions or expectations. One of the factors that influence an individual's career orientation is gender. Problems related to gender or gender greatly affect the achievement of individual career goals, namely in men and women. This research attempts to see the description of career aspiration level of students of gender variables. This study aims to reveal and describe differences in the level of career aspirations of students in terms of gender. The type of research used is descriptive comparative. The hypothesis tested in this study is "There are differences in the level of career aspirations of students in terms of male and female sex". The findings of this study reveal that career aspirations of male and female students are both high-categorized, but there are differences in some indicators. it is hoped that the results of this research can be a guideline for BK teachers in schools in designing career guidance programs for students, as well as to enrich the repertoire of scholarship related to individual career development.